2019
DOI: 10.1021/acs.jafc.9b01933
|View full text |Cite
|
Sign up to set email alerts
|

Biomass-Derived Dialdehyde Cellulose Cross-linked Chitosan-Based Nanocomposite Hydrogel with Phytosynthesized Zinc Oxide Nanoparticles for Enhanced Curcumin Delivery and Bioactivity

Abstract: A sustainable biomass-based nanocomposite hydrogel was formulated, characterized, and applied for curcumin delivery. Phytosynthesized zinc oxide nanoparticles (ZnO NPs) employing musk melon (Cucumis melo) seed extract was embedded in the hydrogel matrices and cross-linked using Dialdehyde cellulose prepared from sugarcane (Saccharum officinarum) bagasse (SCB). Nanoparticle incorporation enhanced the hydrogel's swelling degree to 4048% at pH 4.0. Also, an improved tensile strength of 14.1 ± 0.32 MPa was exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 57 publications
0
33
0
1
Order By: Relevance
“…Their porous structure and swelling property in aqueous media make them suitable for drug loading and delivery. George et al [101] have observed the incorporation of ZnO NPs in dimethyl cellulose crosslinked chitosan hydrogel promoted the drug loading capacity of the gel. They obtained a 30% increment in loading efficiency by incorporating ZnO nanoparticles.…”
Section: Curcumin-metal Oxides Incorporated Hydrogelsmentioning
confidence: 99%
“…Their porous structure and swelling property in aqueous media make them suitable for drug loading and delivery. George et al [101] have observed the incorporation of ZnO NPs in dimethyl cellulose crosslinked chitosan hydrogel promoted the drug loading capacity of the gel. They obtained a 30% increment in loading efficiency by incorporating ZnO nanoparticles.…”
Section: Curcumin-metal Oxides Incorporated Hydrogelsmentioning
confidence: 99%
“…This hydrogel exhibits antimicrobial activity towards Staphylococcus aureus and Trichophyton rubrum. [13] Furthermore, they loaded the curcumin into the hydrogel and studied the diffusion-controlled release mechanism of the loaded drug. Abhishek Gupta et al synthesized the silver nanoparticle by using curcumin-cyclodextrin and incorporated these nanoparticles into the bacterial cellulose (BC) hydrogel.…”
Section: Cellulose-based Antimicrobial Hydrogelmentioning
confidence: 99%
“…The ZnO NPs increase the swelling degree of the hydrogel. This hydrogel exhibits antimicrobial activity towards Staphylococcus aureus and Trichophyton rubrum [13] . Furthermore, they loaded the curcumin into the hydrogel and studied the diffusion‐controlled release mechanism of the loaded drug.…”
Section: Biopolymer‐based Hydrogelsmentioning
confidence: 99%
“…George [265] 2019 Chitosan, Cellulose, ZnO Curcumin 65 FD Monolith Nachverarbeitung Dinu [256] 2016 Chitosan, KlinoptilolithD iclofenac-Natrium, Indomethacin > 70 FD Monolith Nachverarbeitung…”
Section: Indomethacin -F Dp Erlen Nachgelierungunclassified